Energy, Environment and Livelihoods in the Lao PDR : Results from a 2011 Household Survey - Tuominen, Visa; Pasanen, Tytti; Keskiväli, Ilkka; Lakkala, Hanna; Akgün, Orkide; Luukkanen, Jyrki; Kaivo-oja, Jari; Panula-Ontto, Juha (fi=Turun yliopisto. Turun kauppakorkeakoulu|en=University of Turku, Turku School of Economics|, 2019)
This report presents the main results of a household survey collected in 2011. The data was originally collected for FFRC project Interlinkages between energy and livelihoods - Data, training and Scenarios for sustainable energy planning in Laos (INES), funded by the Energy and Environment Partnership (EEP) with the Mekong Region, financed by the Ministry for Foreign Affairs of Finland and the Nordic Development Fund. The demographic profile of the households was surveyed first. The actual questions were related to the following topics: (1) household assets, (2) livelihood activities, (3) income and liabilities, (4) food security and (5) survival strategies, (6) energy use; and (7) environment. This publication is also organized according to these research themes. While the section exploring residential energy use was fairly extensive and utilized throughout the project, the other themes received less attention. The main reason for compiling this e-book was to disseminate all the key results from the survey, especially those with little publicity so far. Similar, recent household level data from Laos is not currently available from any other sources, as far as we know. Thus, this e-Book report provides unique results on the Laotian society and economy based on the household survey findings.